PENGARUH KUALITAS PELAYANAN TERHADAP KEPUASAN PENERIMA LAYANAN ADMINISTRASI DI DINAS KEPENDUDUKAN DAN PENCATATAN SIPIL KABUPATEN BONE BOLANGO - Moh. Rivaldy Moobongu; Juriko Abdussamad; Udin Hamim (Yayasan Panca Bakti Wiyata Pangandaran, 2024)
This study aims to determine the extent to which service quality affects the satisfaction of recipients of administrative services at the Department of Population and Civil Registration in Bone Bolango Regency. The type of research conducted is field research, using a descriptive method with a referential approach. Instrument testing employed validity and reliability tests. Data analysis techniques used include normality tests, coefficient of determination (R) tests, t-tests, and simple linear regression analysis. The results showed that the t-count value is 5.515, while the t-table value is 2.048. Thus, t-count > t-table (5.515 > 2.048) and the significance value is 0.000 < 0.05, indicating that the service quality variable has a significant effect on the public satisfaction variable. The coefficient of determination (R³) resulted in a correlation of 5.21, meaning that service quality affects public satisfaction by 52.1%. The regression equation obtained is Y=35.693+0.446X, meaning that the constant value (a) is 35.693, which indicates that if the service quality value is 0, public satisfaction remains positive at 35.693. The regression coefficient (b) for service quality is positive at 0.446, indicating that for every 1.00 increase in service quality, public satisfaction increases by 0.446.